In the Balance: Indigeneity, Performance, Globalization - H. Raheja, Michelle; J. Phillipson, D.; Gilbert, Helen (Liverpool University Press, 2017)
Indigenous arts, simultaneously attuned to local voices and global cultural flows, have often been the vanguard in communicating what is at stake in the interactions, contradictions, disjunctions, opportunities, exclusions, injustices and aspirations that globalization entails. Focusing specifically on embodied arts and activism, this interdisciplinary volume offers vital new perspectives on the power and precariousness of indigeneity as a politicized cultural force in our unevenly connected world. Twenty-three distinct voices speak to the growing visibility of indigenous peoples' performance on a global scale over recent decades, drawing specific examples from the Americas, Australia, the Pacific, Scandinavia and South Africa. An ethical touchstone in some arenas and a thorny complication in others, indigeneity is now belatedly recognised as mattering in global debates about natural resources, heritage, governance, belonging and social justice, to name just some of the contentious issues that continue to stall the unfinished business of decolonization. To explore this critical terrain, the essays and images gathered here range in subject from independent film, musical production, endurance art and the performative turn in exhibition and repatriation practices to the appropriation of hip-hop, karaoke and reality TV. Collectively, they urge a fresh look at mechanisms of postcolonial entanglement in the early 21st century as well as the particular rights and insights afforded by indigeneity in that process.